2021
DOI: 10.47604/ejbsm.1340
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Customer Focus on Competitiveness of Food and Beverage Manufacturing Firms in Kenya

Abstract: Purpose: Manufacturing firms are critical to the economic growth and development through provision of products and employment. Their competitiveness is therefore critical. The firms have been facing steep competition from foreign companies due to increased globalization. Strategic drivers have been found to be key enablers of firm competitiveness and performance. It is on this basis that the study sought to establish the influence customer focus on the competitiveness of food and beverage processing companies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…This result suggests that customer satisfaction, external communication and information management are significant ingredients of customer focus. This finding is consistent with previous studies, where communication with customers, data management and customer satisfaction were essential principle indicators of project performance in emerging construction firms as all these principles are important parts of the engine driving the project's ability to deliver superior consumer values and superior business performance (Hassan & Waiganjo, 2016;Mehra & Ranganathan, 2008;Muiruri et al, 2021;Pambreni et al, 2019;Williams & Naumann, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…This result suggests that customer satisfaction, external communication and information management are significant ingredients of customer focus. This finding is consistent with previous studies, where communication with customers, data management and customer satisfaction were essential principle indicators of project performance in emerging construction firms as all these principles are important parts of the engine driving the project's ability to deliver superior consumer values and superior business performance (Hassan & Waiganjo, 2016;Mehra & Ranganathan, 2008;Muiruri et al, 2021;Pambreni et al, 2019;Williams & Naumann, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Most studies indicated that inflation have insignificant relationship with manufacturing company's profitability. To mention, on selected macroeconomic indicators on sustainable competitive advantage in food and beverage firms in Kenya: concluded that the inflation, do not have significant effect on profitability [43]. It can be concluded that from this study the general level of inflation does not have significant impact on profitability of manufacturing companies (Table 7).…”
Section: Dynamic Panel Model Estimationmentioning
confidence: 63%
“…However, the adoption of the three programs encountered many challenges which results in the manufacturing sector to face different problems. Among these: low productivity, poor quality of products, imperfect management systems adoption, repeatedly producing same products, unable to improve existing operations, unable to exceed customer expectation, low level of innovation, lower rank favorably against their competitors and low level of production capacity (Dagne, 2009; Muzeyin, 2014; Fasika et al , 2014; Ochiri and Catherine, 2016; Policy Study Institute, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other authors (Dagne, 2009; Muzeyin, 2014; Fasika et al , 2014; Ochiri and Catherine, 2016; Policy Study Institute, 2020) also highlight that the overall performance of the manufacturing industries in terms of productivity (worker and machine), use of new technologies, financial performance, global competitiveness and integrated resource utilizations, level of capacity utilization is found at lower stage. Besides, the authors (Dagne, 2009; Fasika et al , 2014) stated the main reasons for the manufacturing sector to be found at infant stage, it is due to poor infrastructure facility, limited access to finance, limited research and development, poor institutional framework, inadequate managerial and technical skills, improper adoption of CI strategies, poor technological capability and improper resource utilization.…”
Section: Introductionmentioning
confidence: 99%